The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.1004966
|View full text |Cite
|
Sign up to set email alerts
|

Dietary compounds slow starch enzymatic digestion: A review

Abstract: Dietary compounds significantly affected starch enzymatic digestion. However, effects of dietary compounds on starch digestion and their underlying mechanisms have been not systematically discussed yet. This review summarized the effects of dietary compounds including cell walls, proteins, lipids, non-starchy polysaccharides, and polyphenols on starch enzymatic digestion. Cell walls, proteins, and non-starchy polysaccharides restricted starch disruption during hydrothermal treatment and the retained ordered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 118 publications
2
4
0
Order By: Relevance
“…Similar conclusions were observed by Guo et al [37]. Furthermore, non-starch polysaccharides have been identified as α-glucosidase inhibitors capable of binding to the enzyme in competition with starch, thus suppressing starch digestion [38,39].…”
Section: Effects Of Mk's Hydration Rate On Glucose Diffusionsupporting
confidence: 67%
“…Similar conclusions were observed by Guo et al [37]. Furthermore, non-starch polysaccharides have been identified as α-glucosidase inhibitors capable of binding to the enzyme in competition with starch, thus suppressing starch digestion [38,39].…”
Section: Effects Of Mk's Hydration Rate On Glucose Diffusionsupporting
confidence: 67%
“…The rate of starch digestion in breads can also be reduced by incorporating food components that inhibit the ability of amylase to hydrolyze starch, such as dietary fibers and polyphenols (Chi et al., 2022; Giuntiniet al., 2022; Korompokis & Delcour, 2023). For instance, both in vitro and in vivo studies have shown that the digestibility of starch in breads containing natural or added dietary fibers was slower than that of a white bread containing little dietary fiber (Holm & Bjorck, 1992; Rojas‐Bonzi et al., 2020).…”
Section: Reformulating Upfs For Improved Healthmentioning
confidence: 99%
“…For instance, they could cause glucose spikes in the bloodstream after consumption of a meal, which could lead to adverse health effects like diabetes, obesity, and coronary heart disease. Consequently, many of the same strategies can be employed to potentially improve their healthiness, including maintaining the original cellular structures or adding dietary fibers or polyphenols to slow down starch or lipid digestion (Chi et al., 2022). In the case of desserts, which are often soft gels, it may be possible to replace some of the starches and lipids with biopolymer microgels constructed from dietary fibers and/or proteins, which could have health benefits (Shewan & Stokes, 2013).…”
Section: Reformulating Upfs For Improved Healthmentioning
confidence: 99%
“…6,7 In this regard, there is considerable interest in the inhibitory action of natural bioactives on digestive enzymes, such as peptides, phenolic compounds, and flavonoids. 8 Many studies have shown that proteins, protein hydrolysates, and peptides inhibit the activity of starch digestive enzymes and thereby decrease the digestion rate of starch. 9−12 Proteins or protein hydrolysates may inhibit the digestion of starch due to the interactions with starch during heating, forming a physical barrier to hinder the binding or attack by enzymes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Starch is a major glycemic carbohydrate and its digestion behavior is of great nutritional interest, especially as a risk factor for obesity and diet-related chronic diseases. Many starchy foods are considered to have a high postprandial glycemic effect, which is detrimental for people with poor blood glucose management. There is considerable current research aimed at slowing the rate of digestion of starch in foods based on seeking ways to reduce the access/binding of enzymes to starch or to inhibit the digestive enzymes. , In this regard, there is considerable interest in the inhibitory action of natural bioactives on digestive enzymes, such as peptides, phenolic compounds, and flavonoids …”
Section: Introductionmentioning
confidence: 99%